STABILISASI DIMENSI PADA KAYU TANAMAN KARRI (EUCALYPTUS DIVERSICOLOR) DAN JARRAH (E. MARGINATA) BAGIAN I : ASETILASI Dimensional stabilization on regrowth karri (Eucalyptus diversicolor) and jarrah (E. Marginata) Part I : Acetylation - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Wood blocks of karri and jarrah measuring 10 mm (radial) x 25 mm (longitudinal) x 100 mm (tangential) were ovendried for 48 hours at 105°C prior to treatment. Acetylation was carried out in 250 ml- reactor vessels using a 25 % (v/v) solution of acetic anhydride in xylene. Three reaction times, i.e., 8, 16 and 24 hours were used for each wood type. Treatment results are expressed in terms of weight gain (VG) and volumetric gain (VG). The ability of treatment to restrict dimensional changes is expressed as anti swelling efficiency (ASE). Results showed that the weight and volume of both eucalypts specimens substantially increased after acety- lation. In all cases, karri specimens showed higher weight gain, volumetric gain and ASE than jarrah. The effectiveness of acetylation increased with increases in reaction time. Volumetric swelling reduction of more thaw 80% was found in the two regrowth eucalvots.